PENGARUH CITRA MEREK TERHADAP PENGAMBILAN KEPUTUSAN KPR PADA BTN KCP PASURUAN - Dewi L, Rahayu; Akramiah, Nurul; Wahyudi, Paring (Universitas Merdeka Pasuruan, 2017)
The aims of this research is to see how far brand image (physical and psychological factor) effect on decision making to take home loan as well to analyze wich dominant variable from brand image wich influence the decision making to take home loan in BTN KCP Pasuruan. Data in this research was obtained by observing, interviewing and also spreading out the questionnaire to thirty nine respondent. Sample taking techniques is cencus technic. Data analyze on this research using SPSS 22.0 and data testing techniques in this research is using validity test trough significancy test with comparision of r count and r table. Reliability test with alpha cronbach and analysis of multiple linier regression, testing and proving test hypothesis. By utiliting the test of multiple linier regression, the research designaters that variable physical and psychological factor have influence significant on the decision making to take home loan in BTN KCP Pasuruan. The test result of simultan test and partial test (test T and test F). the research prove that all variable (physical and psychological factor) of brand image simultaneously have the significant effect influencing the decision making to take home loan in BTN KCP Pasuruan wich is valued 0.000 < 0.05 . while the dominant variable influencing the decision making to home loan in BTN is the psychological factor. Because value of the significance of psychological factor smaller than physical factor wich value 0.015. Keyword : Physical Factor, Psychological Factor, Decision Making To Take Home Loan